Anabolic hormones and their binding proteins concentrations in female and male elite soccer players in relation to physical perfomance - Zebrowska, A.; Pokora, I.; Poprzecki, S.; Janikowska, G. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: In professional sport, the endocrine responses have been shown to be the most important factors contributing to the athlete`s performance. The mechanism of endocrine factors release depends on the intensity and duration of physical exercise, but little is known about the relationships between hormonal responses and aerobic and anaerobic maximal power in female athletes. The study aimed to analyzed association between exercise-induced growth hormone (GH), testosterone (T), cortisol (C), steroid hormone binding globulin (SHBG), insulin-like growth factor (IGF-1), insulin-like growth factor binding protein-3 (IGFBP-3), catecholamines (E, NE) and some anabolic-catabolic indexes, i.e.: T/C, T/SHBG, and IGF-1/IGFBP-3 in female and male soccer players. The results were compared to maximal power measured during aerobic and anaerobic maximal exercise tests. Methods: Eighteen female (age 19.6 ± 2.6 yrs, training experience 6.9 ± 4.3 yrs) and eighteen male (age 21.8 ± 1.7 yrs, training experience 7.2 ± 2.8 yrs) soccer players participated in the graded aerobic and maximal anaerobic exercise tests. Peak power, maximal oxygen uptake, and peak anaerobic power were measured during the tests. Blood samples were collected for assessment of baseline and post exercise hormones concentrations. Results: The elite female and male athletes demonstrated high level of aerobic performance (VO2max: 43.2 ± 4.8 vs. 54.8 ± 3.7 ml/kg/min; p<001). In male athletes the maximal exercise test induced an increase in post-exercise GH concentrations (p<0.001), IGF-1 (p<0.05), and GH/IGF-1 ratio (p<0.05). Graded exercise test had a significant effect on serum GH and GH/IGF-1 ratio in female athletes (p<0.05). The steroid hormones, IGF-1 levels and IGF-1/IGFBP-3 ratio were significantly higher after cessation of maximal exercise test in male athletes compared to female soccer players. High-intensity exercise elicited an increase of the norepinephrine level in female subjects (p<0.05). A positive correlation was found between the post-exercise GH and peak power and GH/IGF-1 ratio and maximal aerobic power (r=0.68; p<0.01). Discussion: Hormonal status differentially affect physical performance in female and male soccer players. We conclude that growth hormone, GH/IGF-1 ratio, and free fraction of IGF-1 (IGF-1/IGFBP-3) measured during exercise as well as after its cessation might serve as predictors of maximal power and performance in female athletes.